o-Nitrobenzyl Alcohol Derivatives: Opportunities in Polymer and Materials Science - Zhao, Hui; Sterner, Elizabeth S; Coughlin, E. Bryan; Theato, Patrick (Macromolecules, 2012)
Polymers featuring photolabile groups are the subject of intense research because they allow the alteration of polymer properties simply by irradiation. In particular, the o-nitrobenzyl group (o-NB) is utilized frequently in polymer and materials science. This Perspective pays particular attention to the increasing utilization of this chemical group in polymer chemistry. It covers the use of (i) o-NB-based cross-linkers for photodegradable hydrogels, (ii) o-NB side chain functionalization in (block) copolymers, (iii) o-NB side chain functionalization for thin film patterning, (iv) o-NB for self-assembled monolayers, (v) photocleavable block copolymers, and (vi) photocleavable bioconjugates. We conclude with an outlook on new research directions in this rapidly expanding area.